Pengaruh Self Efficacy Terhadap Kemampuan Public Speaking Mahasiswa - Dinda Jatiasih Alimaskus; Roma suryanita Tambunsaribu; Sarina Rulita (CV. ITTC INDONESIA, 2023)
Public Speaking ability is an ability that everyone must have, especially for a student. Public Speaking Ability is the ability of an individual to speak well and confidently to others. This study aims to determine: (1) does Self Efficacy have an influence on public speaking ability in 2021 Communication Science students of Universitas Mercu Buana Yogyakarta, (2), How does Self Efficacy influence the public speaking ability of 2021 Communication Science students of Communication Science Faculty of UMBY. This study uses a quantitative method with the research subject, namely students of Communication Science, Universitas Mercu Buana Yogyakarta class of 2021. Quantitative research method, which looks for the relationship between the two variables. The research data were obtained from the results of distributing questionnaires to 110 communication science students. The data obtained was analyzed using SPSS software. The results showed thatn 33.8% of Public Speaking variables can be explained and influenced by independent variables X1, X2, X3, and X4, while the remaining 66.2% are influenced by other variables that have not been studied.